The queens regnant of Navarre: succession, politics, and partnership, 1274 - 1512 - Woodacre, Elena (Queenship and power, 2013)
"The five reigning queens of Navarre comprise the largest group of female sovereigns in one European realm during the Middle Ages. However, the lives and careers of these important women are largely unknown outside of a regional audience and have never been investigated as a group or in the context of female rule. This groundbreaking survey of Navarre's queens fills this scholarly lacuna, focusing particularly on issues of female succession, matrimonial politics, agency, patronage, and the power-sharing dynamic between the queens and their male consorts. It also highlights the importance of Navarre to the Hundred Years War and other major political events of the era and traces these queens' connections to other female European rulers, including Isabel of Castile and Giovanna II of Naples"--